Concerted action of the FasL/Fas and perforin/granzyme A and B pathways is mandatory for the development of early viral hepatitis but not for recovery from viral infection - Balkow, Sandra; Kersten, Astrid; Tran, Thi Thanh Thao; Stehle, Thomas; Grosse, Philipp; Museteanu, Crisan; Utermöhlen, Olaf; Pircher, Hanspeter; Weizsäcker, Fritz von; Wallich, Reinhard; Müllbacher, Arno; Simon, Markus M. (Journal of virology, 2001)
Cytotoxic T lymphocytes (CTL) play a major role in the recovery from primary viral infections and the accompanying tissue injuries. However, it is unclear to what extent the two main cytolytic pathways, perforin-granzyme A and B exocytosis and Fas ligand (FasL)-Fas interaction, contribute to these processes. Here we have employed mouse strains with either spontaneous mutations or targeted gene defects in one or more components of either of the two cytolytic pathways to analyze the molecular basis of viral clearance and induction of hepatitis during lymphocytic choriomeningitis virus infection. Our results reveal that viral clearance is solely dependent on perforin but that virus-induced liver damage only occurs when both the FasL/Fas and the perforin pathways, including granzymes A and B, are simultaneously activated. The finding that development of hepatitis but not viral clearance is dependent on the concomitant activation of FasL-Fas and perforin-granzymes may be helpful in designing novel strategies to prevent hepatic failures during viral infections.
Gesehen am 26.02.2021